COMBINED APPROACHES TO THE TREATMENT OF ISCHEMIC HEART DISEASE TAKING INTO ACCOUNT MODERATE MITRAL INSUFFICIENCY - Ismatov A. A.; Yarbekov R. R.; Teshayev U. Sh.; Muradov M. M.; Akhmedov H. E. (Web of Journals Publishing, 2025)
A summary of the article's objectives, significance of the problem, and conclusions. For example: "coronary heart disease (CHD) in combination with moderate mitral insufficiency is a complex clinical task that requires a comprehensive approach. The article presents modern strategies of surgical and conservative treatment aimed at improving the prognosis and quality of life of patients."
Keywords: IHD, mitral insufficiency